(untitled) (Revista de Medicina Clinica, 2020)
Introduction: Amyloidosis is a disorder caused by misfolding of autologous protein. Depending on the distribution of amyloid protein, systemic or localized forms are distinguished. Among systemic amyloidosis, there are different forms of pulmonary involvement, which must be taken into account in the differential diagnosis of patients with respiratory semiology. Patients: We propose a case of tracheobronchial localized primary amyloidosis (AL), which raises the differential diagnosis between difficult COPD control COPD and relapsing polychondritis. Outcome: The definitive diagnosis of primary amyloidosis was obtained by bronchoscopy and biopsies. A local treatment was performed with cryotherapy to improve the symptomatology of the patient. A multidisciplinary management was agreed along with hematology. Conclusion: In patients with COPD diagnosis who have a torpid course despite treatment, the diagnosis must be re-evaluated or alternative diagnoses considered. Pulmonary amyloidosis is an uncommon etiology that presents clinical signs similar to obstructive airway diseases and that should be taken into consideration when making a differential diagnosis. Specifically, in localized tracheobronchial amyloidosis, treatment will depend on the patient’s symptoms.